2021
DOI: 10.1590/1980-220x-reeusp-2020-0502
|View full text |Cite
|
Sign up to set email alerts
|

Terminological subset of the International Classification for Nursing Practice for patients hospitalized due to burns

Abstract: Objective: To develop a proposal of a terminological subset of the International Classification for Nursing Practice for burned patients. Method: This is a methodological study following the steps: identification of clinical findings; mapping of terms; construction of statements of diagnoses/results and nursing interventions; content validation of statements; and structuring of the subset with the theoretical model of Basic Human Needs. Content validation was performed by 26 specialist nurses, through the Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
2
1
5
Order By: Relevance
“…The results of validating the statements showed that all ND/ NO/NI achieved a CVI score sufficient for validation (CVI ≥ 0.80); this finding differs from the experience of other similar studies whose data collection was carried out using electronic forms (28,29) .…”
Section: Discussioncontrasting
confidence: 86%
“…The results of validating the statements showed that all ND/ NO/NI achieved a CVI score sufficient for validation (CVI ≥ 0.80); this finding differs from the experience of other similar studies whose data collection was carried out using electronic forms (28,29) .…”
Section: Discussioncontrasting
confidence: 86%
“…Mediante ao exposto, nota-se que a grande maioria dos integrantes da pesquisa sente a necessidade de um instrumento norteador ao atendimento, em busca de uma melhoria na qualidade do atendimento. Dessa forma, destaca-se que a atuação de enfermagem deve ser organizada, de forma que o processo de enfermagem seja imprescindível na prestação de cuidados, requerendo um conhecimento específico da fisiopatologia do agravo, especialmente para detectar problemas e implantar cuidados específicos, além de assegurar maior autonomia à equipe (19) .…”
Section: Discussionunclassified
“…Outro estudo realizado no interior de Minas Gerais (17) relata que o profissional deve estar apto e preparado para o atendimento hospitalar de pacientes grandes queimados, para isso os profissionais devem estar familiarizados com protocolos de atendimento inicial a vítima com queimaduras, Classificações de queimaduras, realização da ressuscitação hídrica do paciente, limpeza adequada, cuidados com feridas, cálculo de superfície corporal queimada (SCQ), coberturas adequadas em queimaduras ,analgesia, antibioticoterapia e aspectos específicos sobre queimaduras (34) . Observou também no estudo que nem todos profissionais possuem estes conhecimentos específicos sobre o cuidado com grandes queimaduras, seja ele por falta de vivência prática, pouco conhecimento e formação inadequada (17) .…”
Section: Fragilidades Do Profissional Enfermeiro Ao Aplicar O Cuidado...unclassified